Atlas of Mineral Deposits Distribution in China (2020) - Qi, Fanyu; Li, Xiaolei; Shang, Yuntao; Meng, Jie; Gao, Xuezheng; Kong, Zhaoyu; Li, Haixin; Yan, Haifei (The China Geological Survey Series,, 2021)
This open access book includes instruction of national mineral database 2020 and atlas of national mineral deposits distribution derived from national mineral database 2020. National mineral database 2020 is based on data from National Geological Archives China(NGAC). Moreover, it introduces the construction method and updates maintenance mechanism of the mineral deposits database and proposes the concept of updating data based on collected archives. The construction guideline on national mineral deposits database provides guiding framework for the future development on geological database. .